Epidermal Electronics: Ultrathin, Stretchable, and Breathable Epidermal Electronics Based on a Facile Bubble Blowing Method (Adv. Electron. Mater. 11/2020). (19th November 2020) - Yang, Xianqing; Li, Lianhui; Wang, Shuqi; Lu, Qifeng; Bai, Yuanyuan; Sun, Fuqin; Li, Tie; Li, Yue; Wang, Zihao; Zhao, Yangyong; Shi, Yixiang; Zhang, Ting
Abstract : A novel bubble blowing method is proposed to fabricate ultrathin, stretchable, and breathable epidermal electronics by Xianqing Yang and co‐workers in article number 2000306 . The ultrathin epidermal electrode can be conformably attached to human skin for high‐quality electromyogram signal recording. It shows the potentiality in applications of future conformal wearable medical devices and human‐computer interfaces.